MENERAWANG MASA LALU DI ERA DIGITAL: FILM SEJARAH VIS A VIS HISTORIOGRAFI - Luqman Abdul Hakim (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2019)
In recent years historical film production or historical films — Historical Film, Historical Movie, Historical Cinema—have become increasingly massive in Indonesia. In its development, historical films in Indonesia are a massive medium to present a past that deserves to be remembered as a collective memory of society. Since the reform era, dozens of historical film titles have been produced and colouring the Indonesian film industry. As a result, many historical films have become references and reference sources for the community to find information about the past. It becomes reasonable to see the development of multimedia-based information technology (audiovisual) which has encouraged the emergence of post-literacy phenomena. In historical studies, historical films can be studied as a thematic study as well as in a methodological realm. As a thematic study, historical films are mental products (mentifact) and social products (sociofact) of society in a certain space of time. Whereas in the methodological realm, historical films can be explored through debates about historical sources or as narratives and representations of the past presented through film media. The study of historical films as a study of history is still a rare and less desirable subject for historians in Indonesia. This paper utilizes literature studies to answer some of the research problems posed. Literature studies of sources related to historical film studies are the focus of the researchers. In addition, a deeper understanding of the development of historical films in Indonesia is also a concern to uncover the souls of the times that surround historical film production. This study concludes that the existence of historical films in the present is a challenge for historians to face the era of openness and variety of media that presents information about the past.